Empowering Women Farmers Tirta Rahayu through Cost of Goods Sold (COGS) Training on Creative Processed Agricultural Products Based on Science and Technologyu through Cost of Goods Sold (COGS) Training on Creative Processed Agricultural Products Based on Science and Technology - Asteria, Beta; Sulastiningsih; Muhammad Subkhan; Rafif Raditya Muhrizal; Dimas Rizky Kurniawan (Edumedia Solution, 2026)
The community service partner is the Tirta Rahayu Women Farmers Group (KWT) located in Tamanan Village, Banguntapan District, Bantul Regency. This group is engaged in the processing of local agricultural products. The main problem faced is the low level of understanding among members regarding how to calculate the Cost of Goods Sold (COGS). This results in inaccurate pricing and inconsistency in profits, meaning that the potential of their business has not been optimally exploited. The empowerment program implemented focuses on training in technology and the use of digital cost analysis tools, particularly spreadsheet applications, to calculate COGS. Through socialization, workshops, and mentoring, there was a 45% increase in members' knowledge of COGS and a 17% increase in production efficiency. As a result, KWT Tirta Rahayu is now able to determine fairer selling prices, optimize resource utilization, and increase the competitiveness of their products in the local market. Mitra pengabdian masyarakat adalah Kelompok Wanita Tani (KWT) Tirta Rahayu yang berlokasi di Desa Tamanan, Kecamatan Banguntapan, Kabupaten Bantul. Kelompok ini bergerak dalam usaha pengolahan hasil bumi lokal. Permasalahan utama yang dihadapi adalah rendahnya pemahaman anggota mengenai cara menghitung Harga Pokok Produksi (HPP). Hal ini menyebabkan penetapan harga jual yang tidak akurat dan ketidakseragaman dalam memperoleh keuntungan, sehingga potensi usaha mereka belum tergarap secara optimal. Program pemberdayaan yang dilaksanakan berfokus pada pelatihan teknologi dan penggunaan alat analisis biaya berbasis digital, khususnya aplikasi spreadsheet, untuk menghitung HPP. Melalui metode sosialisasi, lokakarya, dan pendampingan, terjadi peningkatan pengetahuan anggota tentang HPP sebesar 45% dan efisiensi produksi sebesar 17%. Dampaknya, KWT Tirta Rahayu kini dapat menentukan harga jual yang lebih adil, mengoptimalkan pemanfaatan sumber daya dan meningkatkan daya saing produk mereka di pasar lokal.